2017
DOI: 10.1111/pim.12416
|View full text |Cite
|
Sign up to set email alerts
|

Changes in microRNA expression in response to Schistosoma japonicum infection

Abstract: Schistosomiasis japonicum is one of the most serious zoonotic diseases in the world. There is increasing evidence to show that host miRNAs are modulated following Schistosoma japonicum infection, and some of these miRNAs may play important regulatory roles in response to schistosome infection. Several host miRNAs have been identified and shown to be potential diagnostic biomarkers or novel therapeutic targets for schistosomiasis. These studies have paved the way to a better understanding of the mechanisms of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 66 publications
(140 reference statements)
0
14
0
Order By: Relevance
“…9 Moreover, microRNA-143 also plays an important role in infectious liver disease like hepatitis B, 10,11 hepatitis C 12 and/or Schistosoma japonicum. 13 Although the mechanisms underlying these effects are not fully known, several studies have shown involvement of sprouty3 (SPRY3) 7 and Akt/mTOR pathway 8 in miRNA regulation of gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…9 Moreover, microRNA-143 also plays an important role in infectious liver disease like hepatitis B, 10,11 hepatitis C 12 and/or Schistosoma japonicum. 13 Although the mechanisms underlying these effects are not fully known, several studies have shown involvement of sprouty3 (SPRY3) 7 and Akt/mTOR pathway 8 in miRNA regulation of gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Dai et al have also demonstrated that inhibition of miR‐155 expression may induce HSC activation through ERK1 pathway. Which is more important, Cai et al also reported that miR‐155 exhibited a peak in the liver of mice infected with Schistosoma japonicum and Hong et al have concluded that miR‐155 may be involved in the regulation of hepatic inflammatory responses and the development of schistosomal hepatopathy. In this study, we observed that miR‐155 expression increased in rSjP40‐treated LX‐2 cells (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Identifying changes in miRNA profile in response to parasite infections and the networks these miRNAs regulate is highly informative in explaining immunopathology and may lead to novel therapies to reduce these effects. Mir‐155 and mir‐146 were also among the miRNAs upregulated in the liver following infection with the human‐infective trematode Schistosoma japonicum and, as reviewed by Hong et al., may regulate the inflammatory and T‐ and B‐cell responses to schistosome egg antigens. Several miRNAs have been associated with regulation of hepatic fibrosis, and future studies aimed at testing the effects of mimics of these will be important in determining their potential therapeutic value in reducing liver pathology.…”
Section: Mirna Regulation May Contribute To Immunopathology Of Parasimentioning
confidence: 99%